2018
DOI: 10.1002/cmdc.201800098
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Gold(III) Peptidomimetics: From Synthesis to in vitro and ex vivo Biological Evaluations

Abstract: Five new Au -peptidodithiocarbamato complexes of the type [Au Br (dtc-AA -AA -OR] (in which AA =N-methylglycine (Sar), l/d-Pro; AA =l/d-Ala, α-aminoisobutyric acid (Aib); R=OtBu, triethylene glycol methyl ether), differing with regard to the amino acid sequence and/or the chiral amino acid configuration, were designed to enhance tumor selectivity and bioavailability. The gold(III)-based moiety was functionalized to exploit the targeting properties of the peptidomimetic ligand toward two peptide transporters (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 89 publications
0
15
1
Order By: Relevance
“…In the UV-vis spectra, a hyperchromic effect was observed in the 300 nm band (Figure 4), which is usually associated with the formation of Au-O bonds, something that could point hydrolysis processes. 36 In contrast to the results in PBS buffer, in the presence of DMEM, reactions of reduction were observed for complex 7. Most chemotherapeutic complexes benefit proteins present in bloodstream to achieve its target.…”
Section: Solution Stability Studiescontrasting
confidence: 66%
“…In the UV-vis spectra, a hyperchromic effect was observed in the 300 nm band (Figure 4), which is usually associated with the formation of Au-O bonds, something that could point hydrolysis processes. 36 In contrast to the results in PBS buffer, in the presence of DMEM, reactions of reduction were observed for complex 7. Most chemotherapeutic complexes benefit proteins present in bloodstream to achieve its target.…”
Section: Solution Stability Studiescontrasting
confidence: 66%
“…An extensive number of inorganic and organometallic gold and ruthenium complexes have been conjugated to several different biomolecules for targeted anticancer purposes. These include systems targeting the amino acid transporters [ 102 , 106 , 107 , 108 , 109 ], peptide transporters [ 110 , 111 ], glucose transporters [ 69 , 112 , 113 ], and vitamin transporters [ 77 , 114 , 115 , 116 , 117 , 118 ]. As our review mainly focuses on the emerging receptors for the target delivery of ruthenium and gold complexes into cancer cells, for which the use of biomolecules as delivering carriers is well-known and is out of our scope, we will not discuss them in further detail.…”
Section: Other Emerging Targetsmentioning
confidence: 99%
“…The screenings on some cancerous cell lines demonstrated that the resulting complexes exhibit antiproliferative activities similar to -or, in some cases, higher than -cisplatin. 21 To better investigate the effect mediated by the L-proline moiety on the cytotoxic properties of the gold-DTC compounds, in this work we synthetized and tested both Au(I) and Au(III) derivatives of the L-proline ester dithiocarbamate. We screened our novel compounds for their antiproliferative activity against the HepG2 cell line (human hepatocellular carcinoma), and the apoptosis-resistant HepG2/SB3 counterpart (human hepatocellular carcinoma overexpressing the anti-apoptotic protein SerpinB3).…”
Section: 7mentioning
confidence: 99%